Pengembangan Motorik Halus Melalui Kegiatan Melipat Kertas Pada Anak Didikkelompok B TK Dharma Wanita Tawangrejo Tahun Pelajaran 2015 - Masriah, Siti, Drs. Surtikanti, M.Pd (2015)
This researcs aimed to improve fine motor throught folding. This resears was a classroom action reseacs. The subjects of this study were some learners of groub B In TK Dharma Wanita Tawangrejo academic year 2015. Data analysis using descriptive analysis techniques to compare the comparative with initial conditions the resuls achiefed in each cycle, and a qualitative descriptive analysis results comparing the findings with observation and refleksion on pre-cycle, cicle 1 and cicle II. This resears was a classroom acton resears ( CAR )with the working procedure 2. (two) cycles consisted of your stages, plenning, action, observation. The result showed that students fine motor skills increased. Data kolekston methods observation, field notes and documentation. The researchshowed that evertage child's motor before actionwas 49,37%. After the learning by activity in the cycle of fine motor was 60,82% cycle folding was in the scond 84,78%. Overall, folded activity could improve fine motor skill in groub B TK Dharma wnita tawangrejo.